(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
Phosphoric acid production is of major importance to the Tunisian economy. However, the quality produced is not suitable for other than agricultural use due to mineral and organic impurities. In this study, the purification of industrial phosphoric acid with a maximum P2O5 concentration of 25% was achieved by nanofiltration.Â Six solutions of different P2O5 concentration were used. The removal of organic (total carbon) and inorganic impurities such as magnesium, iron, chrome, zinc, cadmium and vanadium, were studied. The performances of nanofiltration (NF) Nadir NP 30 membrane were determined in terms of permeate flux and P2O5 and impurities retention taking into account the effect of transmembrane pressure, P2O5 concentration and membrane prea-treatment by purified phosphoric acid solution. Results showed that for the industrial 25% P2O5 acid solution, the use of NF membrane achieved a retention of 87.35%, 86.73%, 87.57%, 78.41% and 73.17%, respectively, for iron, aluminum, chrome, magnesium, vanadium and organic matter (kerogen and humic acids) under a pressure of 20 bar. P2O5 permeation increased with the increase of its concentration in the acidic feed solution. The best permeation is provided by 25% P2O5 feeding acid solution which is of almost 98%.